Microhardness and microstructure analysis of the LPBF Additive Manufactured 18Ni300 - Moreno Cerezo, Pablo; Aguilera-García, José Antonio; García-González, Antonio Luis; López-Crespo, Pablo (MDPI, 2024)
This research focuses on analysing the 18Ni300 maraging steel produced through laser powder bed fusion. Specifically, it aims to examine the phase components using X-ray diffraction, the microstructure through scanning electron microscopy, and the hardness of the different structures present in the manufactured material. The primary goal is to meticulously analyse the material and its microstructures. By doing so, a correlation between the hardness and each structure type, be it cellular or columnar, can be established. This will allow us to pinpoint any defects in the material before any surface chemical treatment is carried out and facilitate a thorough examination of its microstructure. A consistent pattern emerges across the samples through systematic measurement of microhardness distribution in various locations and detailed examination of the structure. The findings of the study reveal that the hardness of cellular and columnar structures exhibits a significant variation based on the location of the measurement about cell boundaries. The hardness value is notably higher in the combination of cellular and multiple layers, as the data indicat
Keywords: Microdureza; 18Ni300; Additive manufacturing (AM); Microhardness; Laser powder bed fusion (LPBF); Micro-indentation; Microstructure